Interrogating technological determinism theory and social media usage in political advertising in Nigeria’s electioneering - Michael Enejeta Ilaya; Benjamin Uwaeru Nwanne (Journal of Language, Literature, Social and Cultural Studies, 2026)
The growing dominance of social media in political communication has reshaped how political actors engage voters, yet how technology itself drives these changes remains underexplored, particularly at the sub-national level in Nigeria. This study aims to examine the use of social media in political advertising during state-level elections through the lens of Technological Determinism Theory, focusing on technology as an independent force shaping campaign practices. Adopting a qualitative, descriptive design, the study relies on documentary evidence, existing empirical studies, and systematic analysis of how major political parties and candidates deploy Facebook, Twitter, Instagram, and WhatsApp for campaign communication. The analysis shows that social media has become a central advertising tool, transforming campaign strategies by enabling real-time engagement, personalised messaging, agenda setting, and broad voter mobilisation, especially among young and undecided voters. Technological features such as algorithmic visibility, interactivity, speed, and reach are found to significantly influence political actors’ communication behaviour, reinforcing core assumptions of technological determinism. Nonetheless, the study identifies serious challenges, including misinformation, weak regulatory oversight, ethical dilemmas, and escalating negative campaigning. It concludes by recommending strategic integration of social and traditional media, enhanced voter digital literacy, and robust regulatory frameworks for online political advertising. The study thus fills a key gap by providing a context-specific, technology-driven explanation of contemporary political communication in an emerging democracy.